2012
DOI: 10.1071/mf11172
|View full text |Cite
|
Sign up to set email alerts
|

Invertebrate colonisation during leaf processing of native, exotic and artificial detritus in a tropical stream

Abstract: The relationship between leaf breakdown and colonisation by invertebrates in tropical aquatic ecosystems is poorly understood, especially in regard to the added problem of the potential effects of exotic species. To assess the colonisation by invertebrates during leaf breakdown in a third-order headwater stream in south-eastern Brazil, we conducted an experiment using the native species Miconia chartacea, the exotic species Eucalyptus grandis and artificial leaves. We hypothesised that the quality of the detri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 40 publications
(57 reference statements)
4
39
2
3
Order By: Relevance
“…Capello et al (2004) reported similar observations in his study of the decomposition of leaf-detritus of Salix humboldtiana. Similarly, Gonçalves et al (2012) attributed the changes of the physical state of detritus and faunal composition to the natural degradative succession process: a la llanura aluvial del rio Paraná Medio. Amazoniana,vol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Capello et al (2004) reported similar observations in his study of the decomposition of leaf-detritus of Salix humboldtiana. Similarly, Gonçalves et al (2012) attributed the changes of the physical state of detritus and faunal composition to the natural degradative succession process: a la llanura aluvial del rio Paraná Medio. Amazoniana,vol.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a GLM was performed in the period of the peak colonization, to each functional feeding group, to compare the two types of leaf-detritus. To evaluate the effects of the plant detritus, sampling periods and interaction between these two factors on the functional structure of the community, was used a MANOVA/Pillai Trace test (Scheiner, 2001;Gonçalves et al, 2012).…”
Section: Data Collectionmentioning
confidence: 99%
“…The chemical composition of the leaf influences the selection of plant species by the invertebrate as resource or shelter (Wright & Covich 2005, Graça et al 2001, Gonçalves Junior et al 2006. However, the studies are still not sufficient to help understand the interaction mechanisms between the invertebrate shredders, quality of the litter and temperature in headwater streams.…”
Section: Introductionmentioning
confidence: 99%
“…The role of these invertebrate shredders in leaf breakdown in tropical lotic ecosystems has been explored recently (Wright & Covich 2005, Gonçalves Junior et al 2006, Wantzen & Wagner 2006, indicating the leaves may provide both food and habitat (Ruetz III et al2006, Leroy & Marks 2006, Moretti et al 2009, Gonçalves Junior et al 2012. The chemical composition of the leaf influences the selection of plant species by the invertebrate as resource or shelter (Wright & Covich 2005, Graça et al 2001, Gonçalves Junior et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Mining and shredding groups, for example, are easily found in colonization experiments that use plant detritus as substrate (CLAPCOTT;BUNN, 2003;GONÇALVES et al, 2012;LEITE-ROSSI;TRIVINHO-STRIXINO, 2012). Organisms such as Simuliidae larvae and pupae have a habit of attaching to hard substrates, and are found only in experiments using material such as stones, strips of polyethylene, and expanded clay (PEPINELLI; TRIVINHO-STRIXINO, 2002).…”
Section: Introductionmentioning
confidence: 99%